Comparative Characteristics of Morbidity with Temporary Disability due to Influenza and AURI in the Russian Federation and Moscow in Recent Years - B. A. Zhigarlovsky (Эпидемиология и вакцинопрофилактика, 2019)
Relevance. Acute upper respiratory infections (AURIs) annually cause enormous economic damage due to the incidence of the working population.Aim. Identify the features of morbidity with temporary disability (TD) due to AURIs and influenza in Russia and in Moscow.Materials and methods. A retrospective epidemiological analysis of morbidity with TD due to AURIs and influenza was carried out for the period 2009-2016. Data processing was performed in Microsoft Excel 2013.Results. For the period 2009-2016 in Russia, the proportion of AURIs is up to 73.6% of cases and 66.6% of days of TD from all diseases of the respiratory system, as the cause of TD. In Moscow, the proportion of AURIs for all diseases of the respiratory system accounts is up to 77.9% of cases and 69.3% of TD days. The average duration of a case of TD due to AURIs is 7.9 days (Russia) and 7.3 days (Moscow), and the average duration of a case of TD due to influenza increased in Russia from 8.5 days (2009) to 9.3 days (2016), and in Moscow from 8.4 days (2009) to 9.1 day (2016).Conclusions. Annually, on average, 498,440 cases and 4,382,631 days of TD due to diseases of the respiratory system are not counted in Russia.